Estimation of the distribution of eastern and western marginal localities of plant species in the Southern Tuva Mountain Chain - Artemov Igor’ A. (EDP Sciences, 2021)
The increase of number of the western marginal plant localities is revealed in the western part of the Southern Tuva Mountain Chain, from the Mongun-Taiga Massif to the Sengilen Mt. Range, in comparison with the eastern and central parts of this mountain chain. The increased number of the eastern marginal plant localities is revealed in the eastern part of the mountain chain in comparison of its central part. Such distribution of marginal localities suggests the Southern Tuva Mountain Chain to be a corridor for the westward and eastward migration of plant species.